Propagating topological transformations in thin immiscible bilayer films - Hennessy, M; Burlakov, V; Muench, A; Wagner, B; Goriely, A (Institute of Physics Publishing, 2014)
A physical mechanism for the topological transformation of a two-layer system confined by two substrates is proposed. Initially the two horizontal layers, A and B, are on top of each other, but upon a sufficiently large disturbance, they can rearrange themselves through a spontaneously propagating sectioning to create a sequence of vertical alternating domains ABABAB. This generic topological transformation could be used to control the morphology of fabricated nanocomposites by first creating metastable layered structures and then triggering their transformation. The generality is underscored by formulating conditions for this topological transformation in terms of the interface energies between phases and substrates. The theoretical estimate for the width of the domains is confirmed by simulations of a phase-field model and its thin-film/sharp-interface approximation. © Copyright EPLA, 2014.